2019
DOI: 10.1021/acsenergylett.9b01605
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Stability of Hybrid Halide Perovskites

Abstract: This contribution discusses the chemical stability of methylammonium (MA) halide perovskites (MAPbI 3 , MAPbBr 3 , and MAPbCl 3 ); it considers degradation processes relevant for devices (vs T, O 2 , H 2 O, voltage, illumination) by outlining their thermodynamic constraints and linking them to experimental observations. Thermodynamic considerations indicate that degradation under O 2 is highly favored, albeit in principle preventable by encapsulation. The same is true for H 2 O exposure. Intrinsic degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 89 publications
1
121
0
Order By: Relevance
“…Compared with conventional MAPbI 3 , replacing iodide with bromide (i.e., methylammonium lead bromide, MAPbBr 3 ) has shown higher resistance against environmental humidity. [128,[147][148][149] In addition, the partial substitution of iodide for bromide has shown longer operational lifetimes due to an increased resistance to moisture. [128,150] Pont et al [128] found that higher ratios of bromide in mixed-halide perovskites MAPb(I 1−x Br x ) 3 , resulted in higher moisture stability.…”
Section: Composition Engineeringmentioning
confidence: 99%
“…Compared with conventional MAPbI 3 , replacing iodide with bromide (i.e., methylammonium lead bromide, MAPbBr 3 ) has shown higher resistance against environmental humidity. [128,[147][148][149] In addition, the partial substitution of iodide for bromide has shown longer operational lifetimes due to an increased resistance to moisture. [128,150] Pont et al [128] found that higher ratios of bromide in mixed-halide perovskites MAPb(I 1−x Br x ) 3 , resulted in higher moisture stability.…”
Section: Composition Engineeringmentioning
confidence: 99%
“…CH 3 NH 3 PbI 3 -based perovskite solar cells have been more extensively investigated, due to their fast charge extraction rates and their near-complete visible light absorption, related to a relatively low band gap, around 1.6 eV [11,12]. However, the poor stability of CH 3 NH 3 PbI 3 and rapid degradation in humidity has remained a drawback for its practical application, as a commercialized product [13][14][15][16]. CH 3 NH 3 PbBr 3 constitutes a promising alternative, which presents a good charge transport in devices due to its long exciton diffusion length [17].…”
Section: Introductionmentioning
confidence: 99%
“…Most published studies have examined MAPbI 3 as a representative material. However, optimized solar cells are based on variations of the MAPbI 3 composition that regulate the device stability and as such, the effect of these specific perovskite derivatives on stability must first be understood [47] …”
Section: What Makes Perovskites Unstablementioning
confidence: 99%
“…Apparently, by taking advantage of the hybrid nature of these compounds, utilization of bulky aliphatic or aromatic organic spacer molecules gives rise to 2D materials with improved moisture stability ( Figure 1 ,a–1,b ). Despite the numerous reports towards the assembly of air‐stable solar cell devices, [32,35,38–47] there are limited reports evaluating the inherent environmental stability of 2D perovskite materials either in single crystal form or as a film ( Table 1). Smith et al .…”
Section: Advances On Perovskite Materials Stabilitymentioning
confidence: 99%
See 1 more Smart Citation